Cocoa War: When El Nino Meets Wall Street Capital - Li, Boru (International Journal of Global Economics and Management, 2025)
In 2024, the futures price of cocoa in London soared by 80% within just five months, becoming a rare and volatile event in the global agricultural products market. This paper takes this as the entry point and systematically explores the coupling effect of extreme climate shock and capital market behavior in the formation mechanism of agricultural product prices. Research has found that the main production areas in West Africa have suffered from severe drought and pests and diseases under the influence of strong El Nino, resulting in a 30% to 40% reduction in cocoa production and triggering a global supply panic. Meanwhile, financial speculative forces took advantage of the situation to build positions on a large scale, pushing futures prices to deviate from the fundamentals in a "short squeeze spiral". Based on the theory of warehousing costs, the perspective of financialization and the derivative linkage mechanism, this article analyzes the transmission chain of the sharp increase in cocoa futures prices, and points out that the lagging existing supervision and the vulnerability of the supply chain are the core of systemic risks. Finally, the response strategies proposed include dynamic hedging mechanisms, strengthening of climate financial tools and diversified layout of planting areas, providing theoretical support and policy suggestions for the risk management of similar events in the future.